Smith, Gerald and Aunt Lizzy Ann. Interviews with Gerald Smith (Dildo) and Aunt Lizzy Ann of Green's Harbour. - Baccalieu Trail Heritage Corporation (1994)
This interview is part of a series of filmed oral histories, collected by the Baccalieu Trail Heritage Corporation, from elders who grew up in the area. The Baccalieu Trail Heritage Corporation is a not-for-profit organization dedicated to preserving, promoting and protecting the heritage of the Baccalieu Trail Region. This project collected memories of living and working in the area, going to school, children’s games, home remedies, the first modes of transportation, supernatural beliefs, traditional industries and calendar customs and celebrations. The first interview is with Gerald Smith of Dildo. The interviewer is Damien Cryderman and the interview took place july, 1992. The second interview is with "Aunt Lizzy Ann" of Green's harbour and was recorded in 1995. The interviewer is Rowena Smith. From [00:01-48:12] is the interview with Gerald Smith of Dildo. From [48:15-54:54] is the interview with Aunt Lizzy Ann of Green's Harbour.